2004
DOI: 10.1007/s10695-005-1264-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical Comparison Between sera from the Primary and Secondary Circulations in a Salmonid Fish, Sakhalin Taimen (Hucho perryi)

Abstract: Fish has a unique, non-respiratory vascular system called secondary circulation, which forms capillary networks to the internal and external body surfaces. We compared protein composition in serum from the secondary circulation with that from the primary (blood) circulation. Chromatographic and electrophoretic patterns of sera from the two circulations were essentially same. Immunochemical analysis using specific antibodies against albumin-like protein (a1-protein), immunoglobulin M (IgM), transferrin, vitello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Secondly, their presence may be a result of a leakage from circulating plasma to the mucus. Another mechanism is a phenomenon called "shuttling effect" wherein they are delivered to the mucus via the secondary circulatory system that connects the vascular system, blood and mucus [28,29]. In an earlier study in the permit (Trachinotus falcatus), it has been shown that immune molecules in the skin mucus including anti-protease, lysozyme, alkaline phosphatase, esterase, glutathione peroxidase, catalase, and superoxide dismutase demonstrated day-night profiles; many of which exhibited elevated activity/level during daytime.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, their presence may be a result of a leakage from circulating plasma to the mucus. Another mechanism is a phenomenon called "shuttling effect" wherein they are delivered to the mucus via the secondary circulatory system that connects the vascular system, blood and mucus [28,29]. In an earlier study in the permit (Trachinotus falcatus), it has been shown that immune molecules in the skin mucus including anti-protease, lysozyme, alkaline phosphatase, esterase, glutathione peroxidase, catalase, and superoxide dismutase demonstrated day-night profiles; many of which exhibited elevated activity/level during daytime.…”
Section: Resultsmentioning
confidence: 99%
“…In the present investigation, the administration of bacteria intraperitoneally allowed the pathogens immediate access to the circulation. Therefore, the infected fish displayed an immune response in the skin via alternative ways, that is, (1) one mechanism for plasma proteins to get into mucus is the direct expression of the proteins by the epidermis, or (2) circulating plasma proteins are passively transferred from the secondary circulatory system to the skin mucus during infection [48][49][50]. In the present species, the lysozyme activity level in mucus was consistently higher than that in serum, both in non-challenged and bacteria-challenged groups.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of transferrin in fish mucus could be due to increased expression in epidermal cells as part of the innate immune response following stress (Easy & Ross, 2009). Alternatively, transferrin could leak into the epidermal mucus from plasma through skin abrasion during sampling or through the secondary circulatory system that links together a fish's vascular system and mucus (Tokushima et al , 2004). Transferrin has previously been identified in Atlantic salmon Salmo salar L. 1758 epidermal mucus (Ræder et al , 2007) and was expressed in S. salar and G. morhua epidermal cells (Easy & Ross, 2009; Caipang et al, 2011).…”
Section: List Of Proteins Identified In Epidermal Mucus Of Gadus Morhmentioning
confidence: 99%